2003
DOI: 10.1592/phco.23.12.1245.32701
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Evaluation of Vitamin K1 Therapy to Reverse the Anticoagulant Effect of Warfarin

Abstract: The most frequently prescribed administration routes for vitamin K1 were subcutaneous and intravenous, indicating that the oral route is often not used as recommended. The vitamin K1 doses prescribed for reversal of warfarin anticoagulation were highly variable, and for most (83%) patients, the recommended guidelines were not followed. The clinical significance of noncompliance with the ACCP guidelines for vitamin K1 administration warrants further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
3
7
0
Order By: Relevance
“…These evaluations were all conducted using versions of the ACCP guidelines that preceded the seventh (2004) version, although recent revisions have not been substantive. Utilizing a larger sample size than the majority of these studies [17][18][19][20][21], the results of our study are consistent with these earlier reports, in finding that there is poor adherence to current guidelines, primarily in that doses of vitamin K1 are too high in those whose INR is \9.0, and routes of administration are inappropriate.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These evaluations were all conducted using versions of the ACCP guidelines that preceded the seventh (2004) version, although recent revisions have not been substantive. Utilizing a larger sample size than the majority of these studies [17][18][19][20][21], the results of our study are consistent with these earlier reports, in finding that there is poor adherence to current guidelines, primarily in that doses of vitamin K1 are too high in those whose INR is \9.0, and routes of administration are inappropriate.…”
Section: Discussionsupporting
confidence: 90%
“…The findings in three retrospective reviews have been similar [19][20][21]. Fan found adherence to the ACCP guidelines in only 17% of cases of overanticoagulation; 40% of vitamin K1 doses were administered by SQ injection [19]. Atreja found that adherence to the guidelines decreased as INR increased-from 66 to 36% [20].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…12,13 Van Berkel et al examined the impact of a multifaceted education on improving prescribing practices of vitamin K for warfarin reversal. Their study demonstrated an increase in adherence from 25% to 55.8% after implementation of the education based on the 2008 guidelines.…”
Section: Discussionmentioning
confidence: 99%